Evaluation of the Glymphatic System With Diffusion Tensor Imaging-Along the Perivascular Space in Cancer Pain - Wang, Aibo; Chen, Lei; Tian, Can; Yin, Xiaoyu; Wang, Xinyue; Zhao, Yize; Zhang, Miao; Yang, Lili; Ye, Zhaoxiang (Frontiers in Neuroscience, 2022)
Cancer pain (CP) is one of the most common symptoms affecting life quality, and there is considerable variation in pain experience among patients with malignant tumors. Previously, it has been found that the fluid drainage function in the brain can be regulated by peripheral pain stimulation. However, the relationship between cancer pain and functional changes of the glymphatic system (an important pathway for fluid drainage in the brain) remains unclear. In this study, 97 participants were enrolled, which included 40 participants in the cancer pain (CP) group, 27 participants in the painless cancer (PLC) group and 30 participants in the control (NC) group. Differences in glymphatic system function among the three groups and between before and after pain pharmacological intervention were analyzed by measuring diffusivity and the index along the perivascular space (ALPS index) using diffusion tensor imaging. We found that diffusivity and the ALPS index were significantly lower in the CP group than in the PLC and NC group and increased following intervention with pain relief. Moreover, the ALPS index was negatively correlated with the degree of pain in the CP group. The present study verified that alterations in glymphatic function are closely related to cancer pain, and the quantification of functional changes reflects pain severity. Our findings support the use of neuroimaging biomarkers for cancer pain assessment and indicate that pain can be alleviated by regulating brain function status.